Hubungan Status Gizi Dengan Perkembangan Anak Usia 4-5 Tahun di TK Aisyiyah Bustanul Atfal 2 Labuhan Ratu Baru Kecamatan Way Jepara - Aulia, Alvina Dhea; Dalimunthe, Nathasa Khalida; Hervidea, Radella (CV. Rayyan Dwi Bharata, 2024)
Nutrition is one of the aspects that affects the growth and development of children. Nutritional status is an important health indicator, and vulnerable groups facing nutritional issues include children under five years old. Signs of developmental disorders include slow maturation of nerve cells, delayed motor skills, decreased intelligence, sluggish social reactions, and difficulties in speaking, language, and independence. Nutritional problems in children according to weight-for-age (BB/U) include undernutrition, short stature (TB/U), and underweight (BB/TB). The purpose of this study is to determine the relationship between nutritional status and the development of children aged 4-5 years at Aisyiyah Bustanul Atfal 2 Kindergarten. The subjects of this study are all children aged 4-5 years enrolled at Aisyiyah Bustanul Atfal 2 Kindergarten in Labuhan Ratu Baru Way, Jepara District, totaling 54 children. This study uses total sampling technique. The methodology employed is quantitative research with a cross-sectional design, and data collection was conducted using a microtoise to assess height, a digital scale to measure weight, and the KPSP questionnaire to evaluate nutritional status in relation to child development. The study findings indicate a significant relationship between nutritional status according to weight-for-age (BB/U) and child development (p=0.000) with a strong negative correlation (r= -0.748). There is a significant correlation between nutritional status according to height-for-weight (BB/TB) and child development (p=0.000) with a strong positive correlation (r=0.610). There is also a significant relationship regarding the correlation between nutritional status according to height-for-age (TB/U) and child development (p=0.025) with a weak positive correlation (r=0.304). It is advisable to provide education and early detection of developmental issues in toddlers experiencing nutritional disorders.